2015
DOI: 10.1063/1.4936565
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic rectification of vortex domain wall chirality at nanowire corners

Abstract: The interactions of vortex domain walls with corners in planar magnetic nanowires are probed using magnetic soft X-ray transmission microscopy. We show that when the domain walls are propagated into sharp corners using applied magnetic fields above a critical value, their chiralities are rectified to either clockwise or anticlockwise circulation depending on whether the corners turn left or right. Single-shot focused magneto-optic Kerr effect measurements are then used to demonstrate how, when combined with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Thus, we conclude the small degree of DFD stochasticity observed in a minority of the Tb-doped devices was likely due to variability in the magnetisation structure of injected DWs, as opposed to inherently stochastic interaction of the DWs with the defect sites. This is an important distinction, as many studies have demonstrated the feasibility of controlling the initial structure/chirality of DWs 6,24,50,51 , while the dynamic interactions of DWs with defect sites is inherently uncontrollable at fields above H WB…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we conclude the small degree of DFD stochasticity observed in a minority of the Tb-doped devices was likely due to variability in the magnetisation structure of injected DWs, as opposed to inherently stochastic interaction of the DWs with the defect sites. This is an important distinction, as many studies have demonstrated the feasibility of controlling the initial structure/chirality of DWs 6,24,50,51 , while the dynamic interactions of DWs with defect sites is inherently uncontrollable at fields above H WB…”
Section: Resultsmentioning
confidence: 99%
“…Together these pushed the VDWs through the double notch and caused them to pin just beyond the current line's edge, allowing their final chiralities to be determined. This relatively complex protocol was required so that we could place the VDWs in locations where they could be imaged, without causing them to interact with geometric features (e.g., corners, larger notches) that could induce additional modifications of their chiralities …”
Section: Resultsmentioning
confidence: 99%
“…Although recent research has focussed more on nanowires with PMA materials 6 , 7 , DWs in IPM nanowires remain interesting. This is because of the extra degree of freedom provided by DW chirality that can be utilized for information processing 8 10 and in controlling switching trajectories in interconnected structures such as the Kagome spin-ice architecture 11 , 12 . DWs in IPM nanowires have also been proposed for use in more novel applications including conveying magnetic beads in biomedical applications 13 , and manipulating ultra-cold atoms 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%